IMPLEMENTASI PENDIDIKAN KADER MUHAMMADIYAH DAN NU DALAM MENGUATKAN KARAKTER RELIGIUS DAN KEPEMIMPINAN DI LEMBAGA PENDIDIKAN ISLAM (Studi Multikasus di SMK Al Inabah Ponorogo dan SMK Ma’arif Dolopo Madiun) - Mita Cahyani; Nurul Iman; Nuraini Nuraini (TARBAWI:Journal on Islamic Education, 2019)
Al Inabah Ponorogo Vocational School is a school that stands under the auspices of Muhammadiyah, while Ma'arif Dolopo Vocational School Ma'arif Dolopo Vocational School is a school that stands under the auspices of the Nahdlatul Ulama (NU). Both of school develops by depriving character of human resources, competent, independent, love the environment and have a global outlook, in accordance with the vision and mission proclaimed. The purpose of this study was to find out the educational concepts of Muhammadiyah and NU cadres in strengthening religious character and leadership in Islamic Education Institutions and to know implementing education for Muhammadiyah and NU cadres in strengthening religious character and leadership in Islamic education institutions. This study was designed using a comparative descriptive research approach with the type of case study and multi-site design. Data collection using interview, observation and documentation techniques. While the data analysis techniques using data reduction, data display, verification.